The Horizontal Bearing Capacity of Composite Concrete-Filled Steel Tube Piles - Yunxiu Dong; Zhongju Feng; Haibo Hu; Jingbin He; Qilang Zhang; Fuchun Wang (Advances in Civil Engineering)
Steel casings (SCs) are extensively and increasingly used to stabilize the borehole wall in the construction of bridge pile foundations. Steel casings (SCs), together with reinforced concrete piles (RCPs), form composite concrete-filled steel tube piles (CCFSTPs), which differ significantly from ordinary RCPs in horizontal bearing capacity. In this study, based on the characteristics of CCFSTPs, the horizontal bearing capacity of a CCFSTP was examined through a centrifugal model test with the length of the steel casing (LSC) and the modulus of the soil mass in the steel casing soil compaction zone (ESCSC_zone) as variables. Pile-side soil resistance, load-displacement curves, and pile moment curves were obtained for the CCFSTP. The results show that increasing LSC within a range of 12 cm significantly increases the ultimate horizontal bearing capacity of the CCFSTP, and further increasing LSC beyond 12 cm produces a continuous increase in the ultimate horizontal bearing capacity of the CCFSTP but only to an insignificant extent. In addition, increasing ESCSC_zone increases the ultimate horizontal bearing capacity of the CCFSTP, but to a relatively small extent. The results of this study provide a theoretical basis and technical support for the design and construction of CCFSTPs.